A Comparative Analysis of Stock Returns Before and After Stock Split in Companies Listed on the Indonesia Stock Exchange - Vhasco AG. Siagian; Rahima Br Purba; Soulthan Saladin Batubara (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study aims to analyze the comparison of stocks return before and after the activity of a stock split. The data used in this study are secondary data from the Indonesia Stock Exchange (IDX). Using purposive sampling method with certain criteria obtained a sample of 75 companies, this study uses event studies with observation periods 7 days before and 7 days after stock split to determine the information content contained in an event. Hypothesis conducted in this study uses the normality test and the Wilcoxon signed rank test. The results of testing the hypothesis in this study indicate that there are no differences in stocks return between before and after the activity of a stock split.